Clinical classification of brow ptosis - Daniel Sundfeld Spiga Real; Rodrigo Pacheco Reis; Roney Gonçalves Fechini Feitosa; Elvio Bueno Garcia; Masako Ferreira (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: The study of the eyebrow is a great challenge for plastic surgery because of its complex relationship with facial structures. The present study aims to describe a clinical classification of brow ptosis. METHODS: A cross-sectional study with patients of both sexes and ages ranging from 18 to 100 years, subdivided into 3 groups according to age. Group 1: 18 to 30 years of age, Group 2: 31 to 60 years of age, and Group 3: 61 to 100 years of age. Three measurements were taken on each side by different examiners blinded to each other's results. RESULTS: A total of 90 patients, with ages ranging from 18 to 94, including 39 (43.3%) men and 51 (56.7%) women, were studied. Group 1, with a mean age of 26.7 years was considered normal, with mean brow ptosis of 2.14 cm. In Group 2, with a mean age of 44.2 years, the mean brow measurement was 1.9 cm. In Group 3, the mean age was 72.6 years and the mean brow measurement was 1.27 cm. The table outlining the brow ptosis classification assigns a degree of ptosis to each interval, ranging from I to IV. Each degree was correlated with a numerical range in which > 1.8 cm is normal, 1.7-1.5 cm corresponds to degree I ptosis, 1.4-1.2 cm to degree II ptosis, 1.1-0.9 cm to degree III ptosis, and < 0.8 cm to degree IV ptosis. Surgery was indicated for degrees II, III, and IV. CONCLUSION: The objective measurement of brow tail position enabled classification of the degree of ptosis and guides surgical decision-making.